2012
DOI: 10.1590/s0037-86822012005000005
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective serologic survey of hantavirus infections in the county of Cássia dos Coqueiros, State of São Paulo, Brazil

Abstract: Our results showed that hantavirus infections occurred in Cássia dos Coqueiros, completely unrecognized, even before hantaviruses were described in the Americas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
8
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
(9 reference statements)
4
8
0
4
Order By: Relevance
“…Another study, conducted in cities in the State of Santa Catarina near the border between Brazil and Argentina (Souza et al, 2011), found a much higher seropositivity (3.5%) for IgG antibodies to hantavirus compared with our study; however, most of the HCPS have occurred in this country's southern and southeast regions. Additionally, a retrospective research of hantavirus infection that was performed slightly closer to our region, in the city of Cássia dos Coqueiros, State of Sao Paulo, found positive results in 4.7% of the samples (Badra et al, 2012). Lastly, in another South American study in Chile, the researchers found a similar seroprevalence (0.72%) of antibodies to the Andes virus (Frey et al, 2003).…”
Section: Discussionsupporting
confidence: 60%
“…Another study, conducted in cities in the State of Santa Catarina near the border between Brazil and Argentina (Souza et al, 2011), found a much higher seropositivity (3.5%) for IgG antibodies to hantavirus compared with our study; however, most of the HCPS have occurred in this country's southern and southeast regions. Additionally, a retrospective research of hantavirus infection that was performed slightly closer to our region, in the city of Cássia dos Coqueiros, State of Sao Paulo, found positive results in 4.7% of the samples (Badra et al, 2012). Lastly, in another South American study in Chile, the researchers found a similar seroprevalence (0.72%) of antibodies to the Andes virus (Frey et al, 2003).…”
Section: Discussionsupporting
confidence: 60%
“…Serologic surveys performed on inhabitants of urban areas with positivity ranging around 1%-4% also confirmed that the virus is circulating in these areas and probably the majority of infections have an asymptomatic course [16][17][18].…”
Section: Types Of Hantavirus In Brazil and Their Epidemiological Detementioning
confidence: 72%
“…In another study conducted in cities near the border between Brazil and Argentina, still in the State of Santa Catarina, they found a 3.5% seroprevalence 11 . The highest reported level of infection with an index of 4.7% was found in the City of Cássia dos Coqueiros, located in the State of São Paulo, in the Southeast region 12 . It is important to point out that most of the HCPS cases occurred in the Southeast of the country, along with the South region.…”
mentioning
confidence: 91%